INTERIOR DESIGN PRINCIPLES OF INCLUSIVE PRESCHOOLS - Qiao, Dan; Bulhakova, T. V.; Lu, Yingjian (Art and Design, 2023)
The aim of this study is to identify the principles of shaping the interior of an inclusive preschool for children aged 3–6 years based on an analysis of modern ideas of inclusive kindergarten design and research in child behavioral psychology. Methodology. The following theoretical and specialized research methods are used in this study: analysis of literary sources and normative literature on the research topic, comparative analysis of projects implemented within the framework of inclusive kindergartens, and methods of systematization, synthesis, and data generalization. Results. The study has identified six fundamental principles for shaping the interior of an inclusive preschool for children aged 3–6 years. These principles are based on both child behavioral psychology and modern practices in designing kindergarten interiors. The identified principles are the “principle of openness”, “principle of difference”, “principle of creativity”, “safety principle”, “principle of fun”, and “principle of naturalness”. By utilizing these principles, a modern methodology for interior design of inclusive kindergartens can be developed, which will include specific techniques for each principle. The outcome will be a space that provides children with a sense of security, comfort, interest and contributes to their overall harmonious development. Scientific novelty. The study presents the principles for interior design of inclusive preschools, which will aid designers in creating a harmonious and inclusive kindergarten space that supports the comprehensive development of a child’s personality. This study advances the development of interior design for inclusive kindergartens, taking into account new societal needs in modern conditions. Practical significance. The findings of this research have practical implications for the field of interior design in inclusive kindergartens as well as for students in the Environmental Design program. The identified principles can serve as a guide for designers in creating a harmonious and inclusive space that promotes the comprehensive development of children.